Persistence of Profit in Energy Industry: Dynamic Evidence from Turkish Companies - Gozbasi, Onur; Aslan, Alper (International Journal of Economics and Financial Issues, 2015)
One of the main lacks of the profit persistence literature is the fact that it focuses on only manufacturing, banking and food industries. This study, for the first time, extends the literature by considering the intensity of competition in 13 energy companies from 1997 to 2011 in Turkey as an emerging market. The results show that the degree of persistence is higher in the energy industry mainly due to a low degree of market saturation, weak price competition and a lowly concentrated retailing industry, thus providing no support for the hypothesis that there is a lower persistence of profits in emerging markets due to more intense competition in Turkey. Keywords: Persistence of Profit; Energy Industry, Competition JEL Classifications: C22; G30; L10